Transformasi UMKM: Pendampingan pemasaran dan teknologi untuk pertumbuhan ekonomi lokal - Asri Ainun; Suherman (Jurnal Dedikasi Masyarakat, 2020)
To increase the resilience of micro, small, and medium enterprises (MSMEs) amidst the impact of the Covid-19 pandemic, the Development Study Program at Muhammadiyah University Parepare has carried out assistance in Cilellang Village, Mallusetasi District, Barru Regency. The main focus is on the traditional cake service sector. This assistance introduces innovation and production efficiency through training in machine use and online marketing strategies. Program evaluation shows positive results with increased marketing understanding and technology adoption by MSME players. The most striking impact is the increase in cake production efficiency thanks to the use of machines and market expansion through online marketing. Thus, this assistance not only overcomes marketing obstacles in the pandemic but also opens up opportunities for local economic growth.